Effect of Low Dose Lead (Pb) Administration on Tail Immersion Test and Formalin-induced Pain in Wistar Rats: Possible Modulatory Role of Cobalt (II) Chloride (Nigerian Journal of Physiological Sciences, 2021)
Summary: Lead (Pb) is cheap and there is a long tradition of its use, but its toxic effects have also been recognized. There is increased public health concern regarding the hazards of low dose Pb exposure to adults and children. Studies have shown the risks for hypertension, decrements in renal function, subtle decline in cognitive function, and adverse reproductive outcome at low blood Pb level. In this study, the possible modulatory role of cobalt (II) chloride (CoCl2) on low level Pb exposure on tail immersion test and formalin induced pain was investigated. Twenty adult Wistar rats of both sexes (weight 150g to 200g) were used. The animals were divided into four groups (n = 5) and administered Pb (5mg/kg), Pb (5mg/kg) + CoCl2 (50mg/kg) and CoCl2 (50mg/kg) orally for twenty-eight days. The last group served as control and were given distilled water only. In the tail immersion test, there was no significant change in reaction time for all three groups when compared to the control. In the formalin-induced pain, pain score after five and forty-five minutes also do not show significant change for all the three groups when compared to control. This work suggested that exposure to 5mg/kg Pb for twenty-eight days do not significantly impair reaction time in tail immersion test and pain score in formalin induced pain in Wistar rats. Also, administration of 50mg/kg CoCl2 do not improve performance of the animals in the experiments.